Diseño de un sistema inteligente para la recolección de desechos sólidos en ciudades pequeñas y medianas - Jaramillo Montaño, Luis Enrique (2017)
The present titling work shows the design of a solid waste collection system based on lateral loading containers, which serve to optimize the resources using the best path determination using the JAVA software that allows its collection, additionally it incorporates a file record that makes possible a future design based on the needs of sectors, in order to optimize the proposed model. For the development of the project several studies were carried out, among which are: Study for the elaboration of a model of collection and recycling of side load containers based on already existing models. Study for the elaboration of a prototype capable of realizing the meaning and the cost of the percentage of filling of a container based on its cost and functionality. Study to perform the information process from the data acquired by the prototype to the graphic representation in a smart device. The computer tools used for the development of the work son: Arduino, Proteus, NetBeans, MySQL, Android Studio, SolidWorks.